'Better policies for better lives'?: constructive critique of the OECD's (mis)measure of student well-being - Rappleye, Jeremy; Komatsu, Hikaru; Uchida, Yukiko; Krys, Kuba; Markus, Hazel (Journal of education policy, 2020)
Facing increasing critique that PISA focuses too narrowly on cognitive achievement and human/knowledge capital, the OECD has recently shifted some of its focus to student happiness. The 2017 Students' Well-Being report distinguishes between 'happy schools' and 'unhappy schools', showing that among students who combined high performance and life satisfaction, northern European countries topped the charts. Meanwhile, students in East Asian countries including Japan, China, Taiwan, Hong Kong, and Korea registered the lowest 'life satisfaction' scores among all participating countries. This piece points out some of the problems inherent in the OECD's recent turn to happiness, problematizing the OECD yardstick of life satisfaction. Attempting to keep the critique constructive, we suggest that the OECD may want to consider using alternative metrics, then briefly highlight one developed in East Asia from different first assumptions: the Interdependent Happiness Scale. In conclusion we flag, but cannot answer, some related educational questions concerning policy, pedagogy, and priorities for the future.